Gilbert’s Syndrome: Terminology, Epidemiology, Genetics, Pathogenesis (Part I) - T.V. Sorokman (Zdorovʹe Rebenka, 2016)
The aim of the review was the analysis of the literature about the prevalence, etiology, genetics and pathogenesis of Gilbert’s syndrome (GS). The scientific literature regarding GS with the keywords «Gilbert's syndrome», «hyperbilirubinemia», «uridine diphosphate glucuronosyltransferase (UGT-1A)» using PubMed as a search engine was reviewed. The abstracts of 75 articles, based on investigations held within the last 10 years were analyzed. The criterion for the selection of articles for the study was based on their close relevance to the topic. The results of researches covered in 10 articles and two reports were of the top interest and deep study. In medical literature GS is described under the names of different syndromes: Gilbert’s syndrome, Meulengracht’s syndrome, Gilbert — Meulengracht syndrome, Gilbert — Lereboullet syndrome, and also such as: constitutional hepatic dysfunction, familial nonhemolytic jaundice, Gilbert’s type of hyperbilirubinemia, idiopathic unconjugated hyperbilirubinemia, Crigler — Najjar hyperbilirubinemia, Arias’ type (HBLRCN, hyperbilirubinemia I). GS is a predominantly hereditary unconjugated hyperbilirubinemia associated with the reduced activity of uridine diphosphate glucuronosyltransferase (UGT-1A) in liver, which is encrypted in external resources as ICD-10 — E80.4; OMIM — 143500; DiseasesDB — 5218; MedlinePlus — 000301; eMedicinemed — 870; MeSHD — 005878. UGT-1A isoforms are found in different parts of the gastrointestinal tract (UGT1A1, UGT1A3, UGT1A4, UGT1A6), in the liver — UGT1A9, in the esophagus and stomach — UGT1A7, in the esophagus and intestines — UGT1A8, in the esophagus, bile ducts, stomach, intestines — UGT1A10, in kidneys — UGT1A19. The patients with GS have signs of disorders in all phases of metabolism of bilirubin — from its production to excretion: the lack of bilitranslocase which is responsible for the capture of bilirubin from the blood and its transport to hepatocytes, the deficit of Y- and Z-protein ligand (glutathione-S-transferase enzyme), responsible for transport of bilirubin to microsomes, the deficiency of UGT-1A, which provides the transfer of glucuronic acid to bilirubin. The prevalence of the mutant gene in European countries reaches 35–40 %, in certain ethnic groups in Africa more than 50 %, in Asian countries it is slightly lower (16–33 %). The prevalence of GS in Ukraine has not been studied. The ratio of male and female patients with GS is 3–4 : 1. The main reason of the lack of the enzyme is mutation of the gene encoding UGT1A1, however, the other factors are also responsible for the development of the syndrome and manifestation of its symptoms (male gender, additional gene mutations: c.993 (p.Q331H); *6 (c.211G > A); (nt-211, nt-686, nt-1,091 and nt-1456). The specific polymorphism in candidate genes was identified (SLCO1B3 ABCC2 and NUP153). The histological and ultrastructural features of GS include normal hepatic lobules and deposition of bile pigment granules in hepatocytes. Signs of the hepatosis are seen at later terms and serve as evidence of the evolution of the disease.